Former employees of foreign MNEs boost incumbent workers' wages in domestic firms? - Eoin T. Flaherty (University College Dublin, UCD School of Economics, 2022)
This paper examines evidence on wage spillovers from workers with experience in foreign multinational enterprises (MNEs) to incumbent workers in domestic firms. Using administrative panel data from Ireland, I examine possible heterogeneity for such spillovers across the wage distribution using quantile regressions. I begin by using existing methodology and find that, once industry-year and region-year dummies are added as control variables, the average wage spillover effect on incumbents from former foreign MNE workers moving to domestic firms disappears. The quantile results suggest that there are positive spillovers for incumbent workers in the top 40 percent of the wage distribution only. This indicates that foreign MNEs increase inequality through spillovers to domestic firms via labour mobility.
Keywords: F16; F23; J31; J60; 330; foreign direct investment; spillovers; labor mobility; linked employeremployee data; wages